Kemampuan Berbicara Produktif Terhadap Keterampilan Menceritakan Pesan Moral Cerita Rakyat Sampuraga Karya Puspasari Setyaningrum - Siregar, Nur Azizah; Parapat, Lili Herawati; Afifah, Nur (Jurnal Hata Poda, 2023)
This study aims to describe the results of the influence of productive speaking skills on the skills of telling the moral message of the folklore Sampuraga by Puspasari Setyaningrum by students of SMA Negeri 1 Angkola Barat. This research was conducted in class X SMA Negeri 1 Angkola Barat located in the village of Sitinjak. Addressed at Jl. Sibolga, Sigumuru, Kec. West Angkola, South Tapanuli Regency, Prov. North Sumatra. The research method that the author uses is a descriptive method with a quantitative approach. Descriptive method, using a multiple choice test variable X 10 questions and essay variable Y 5 questions. The population of this study consisted of six classes of students in class X totaling 185 students. There are two stages carried out, namely descriptive analysis, statistical analysis. Based on the results of the study, it is known that there is a significant influence between the ability to speak productively on the skills of telling the moral message of the Sampuraga folklore by Puspasari Setyaningrum by class X students of SMA Negeri 1 Angkola Barat. This can be seen in the hypothesis testing carried out on the data found, where the hypothesis alternative (ha) in this study is accepted, namely (ho) is rejected.Keywords: Productive speaking, moral messages.